Chemotherapeutic Role of Bis-3-azophenyl-4-hydroxy-6-methyl-pyran-2-one Iron(II) in Chemically Induced Skin Cancer in Albino Rats - Shahid, Samina; A. Qureshi, Fahim; Adnan, Ahmad; Rehman, Shafiq-ur (Asian Journal of Chemistry, 2011)
The present study was designed to observe the effect of bis-3-azophenyl-4-hydroxy-6-methylpyran- 2-one iron(II) in 7,12-dimethylbenz-(a)anthracene (DMBA) followed by 12-Otetradecanoyl- phorbal-13-acetate (TPA), induced chemical cacinogens on the skin of albino rats. Eighty albino rats were divided into four groups. First and second groups (A & B) were used as control. In third group C, 7,12-dimethylbenz(a)anthracene was given 100 mg/mL as single dose while 12-O-tetradecanoyl-phorbal-13-acetate was given 10 mg/mL in acetone twice a week. Different types of tumors were observed. In group D, all the chemical carcinogens (7,12-dimethylbenz(a)anthracene and 12-O-tetradecanoyl-phorbal-13-acetate) were applied locally in the same dose, route and schedule, after the induction of skin cancer, the complex (bis-3-azophenyl-4-hydroxy-6-methyl-pyran-2-one iron(II)) was applied by following the same route.